2016
DOI: 10.1016/s2214-109x(15)00322-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of acute kidney injury in children and adults in sub-Saharan Africa: a systematic review

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
240
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(281 citation statements)
references
References 38 publications
32
240
9
Order By: Relevance
“…Besides, the proportion of infection was significantly higher in HIV-infected persons, as observed in the other series [14]. Water losses related to diarrhea and/or vomiting and gastrointestinal fungal…”
Section: Etiologysupporting
confidence: 62%
“…Besides, the proportion of infection was significantly higher in HIV-infected persons, as observed in the other series [14]. Water losses related to diarrhea and/or vomiting and gastrointestinal fungal…”
Section: Etiologysupporting
confidence: 62%
“…This shortcoming is highlighted well in the study by Olowu et al 21 This systematic review of AKI, with a focus on sub-Saharan Africa, documents that, in 3,340 patients admitted to hospital with AKI in 13 countries in the region, the disorder was severe in most cases, with indications for dialysis in 66% of children and 70% of adults. However, only slightly more than half of children and one-third of adults received dialysis when required.…”
Section: Obstacles To Diagnosis and Treatment Of Aki In Developing Comentioning
confidence: 99%
“…This role is particularly important since the density of physicians is 0.02-0.29 per 1,000 people in many African countries, which is ten to 100 times lower than the target of the World Health Organization. 22 The study by Olowu et al 21 also showed that ~80% of children and adults with AKI in sub-Saharan Africa who required, but did not receive, dialysis die. Major barriers to access to care were erratic hospital resources and out-ofpocket costs.…”
Section: Obstacles To Diagnosis and Treatment Of Aki In Developing Comentioning
confidence: 99%
“…AKI is a common reason for admission in intensive care unit (ICU) and its incidence increases with age (17). Infections, toxics and obstetric gynecological pathologies are the main causes of AKI in African series (6). According to Baraldi et al, drugs (35.7%) and renal hypoperfusion (30.2%) are the main etiologies in the West.…”
Section: Discussionmentioning
confidence: 99%
“…causes are dominated by infections, toxic and obstetric gynecology causes are responsible (6). AKI may occur at any age.…”
mentioning
confidence: 99%